PENGARUH KONFLIK BONDHOLDERS-SHAREHOLDERS, BONUS PLAN DAN POLITICAL COST TERHADAP KONSERVATISME AKUNTANSI (Pada Perusahaan Manufaktur Sub-Sektor Industri Konsumsi Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Maria Ulfa; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this research is to examine the effect of conflict ofstakeholders, bonus plan and political cost to accounting conservatism. Thepopulation in this study is a manufacturing company sub-sector of theconsumption industry listed on the Indonesia Stock Exchange period 2013-2016.The sampling technique in this study used purposive sampling and obtained 19samples of companies used as criteria manufacturing companies sub-sector of theconsumption industry listed on the Indonesia Stock Exchange period 2013-2016.Sources of data from this study came from Indonesia Stock Exchange (IDX),www.idx.co.id. The method of analysis used in this study is the classicalassumption test, and hypothesis test and multiple linear regression.The results of this study indicate that: 1) Based on the test onsimultaneous or F test is known that the variables conflict of bondholdersshareholders, bonus plan and political cost have a significant positive effect onaccounting conservatism. 2) Conflicting variables of bondholders-shareholders,bonus plans, and political costs together 67.2% influenced the accountingconservatism of manufacturing companies sub-sector of the consumption industrylisted on the Stock Exchange and 32.8% explained by other factors not mentionedin this study. 3) Partially conflict variable of bondholders-shareholders, bonusplan and political cost have a significant positive effect to conservatism ofaccounting manufacturing company sub-sector of consumption industry listed onBEI.Keywords: Conflict of bondholders-shareholders, bonus plan, and political cost.